B Lymphocyte Subsets in Children With Steroid-Sensitive Nephrotic Syndrome: A Longitudinal Study - Ling, Chen; Chen, Zhi; Wang, Xiaolin; Hua, Lin; Gui, Jingang; Liu, Xiaorong (Frontiers in Pediatrics, 2021)
Abstract Background B-cell subsets may be involved in the pathogenesis of childhood steroid-sensitive nephrotic syndrome (SSNS). Horizontal control (HC) studies have shown that homeostasis of B-cell subsets changes at different stages of the SSNS. However, there is a lack of longitudinal studies that have investigated dynamic changes in B cell subpopulations. Methods Blood samples were collected at the following time points from 15 children with SSNS treated at our hospital : before administration of steroid and after 3 days, 1 week, and 3, 6 , 9, and 12 months. The proportions of circulating total B cells (CD19+), transitional B cells (CD19+CD24highCD38high), mature B cells (CD19+CD24lowCD38intermediate), and memory B cells (CD19+CD24highCD38-) were monitored by flow cytometry. Results The proportion of CD19+ B cells before steroid administration was significantly higher than that observed at any other time point and in the HC group (p<0.001). This proportion was significantly lower than that in the healthy control group at 12 months (p=0.031). Transitional B cells before (%BL 9.5±4.4) and 3 days after steroid administration (%BL 10.6±5.1) were significantly higher than at any other time point and in the HC group (p＜0.001). Although these cells declined after the 3rd day the percentage was still significantly lower than that of the HC group at 12 months (p=0.029). Memory B cells increased gradually after steroid administration and decreased to the normal range after 9 months. Conclusions B cell subpopulations show dynamic changes in children with SSNS, suggesting that they are involved in the pathogenesis of the disorder. Further studies are required to determine whether this change can guide individualized treatment.